SOSIALISASI BAHAYA PENGGUNAAN PLASTIK SEBAGAI WADAH MAKANAN DAN MINUMAN TERHADAP KESEHATAN MASYARAKAT DI DASAWISMA MERPATI DESA SIDODADI - Yusri Nadya; Nurlaila Handayani; Yusnawati; Nina Fahriana; Lely Masthura (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2023)
Plastic containers are an alternative choice for the most widely used people as food and beverage packaging. According to research, the use of plastic that does not meet the requirements will cause various health problems, because it can trigger cancer and damage to tissues in the human body (carcinogenic). The lack of public knowledge about the dangers of plastic as a food container and the use of inappropriate plastic is a factor in the use of plastic which is sometimes not in accordance with its designation. For this reason, socialization and education are needed to know about the main types of plastic. This service was held at Dasawisma Merpati, Sidodadi Village, attended by 36 Dasawisma members. The community service program for outreach and education on the dangers of plastic for food and beverage containers is well implemented. This is evidenced by the participation of Dasawisma members and their understanding of the material. It was concluded that this educational program effectively modifies participants' attitudes and knowledge regarding the risks of using plastics in the processing and packaging of food and beverage products.